Improvement in the cases of hypertensive disorder of pregnancy with help of HDP-gestosis score - Imam, Syeda Tuba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: An assessment tool for the risk of pre-eclampsia is the HDP-gestosis score, which has a range of scores from 1 to 3. A pregnant woman is classified as "at risk for pre-eclampsia" and treated appropriately if her overall score is 3 or higher. In order to predict pre-eclampsia, it is necessary to assess the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of the HDP-gestosis score. Methods: From January 2022 to December 2022, 109 pregnant patients who presented at the obstetrics and gynaecology department were included in this prospective research. The patients’ risk of developing pre-eclampsia was evaluated after 20 weeks of pregnancy. We collected information on the patient’s age, gravida, obstetric history, menstrual cycle regularity, polycystic ovarian disease history, length of marriage, parity, prior medical and surgical intervention, prior/current pharmaceutical use, and family history. Gestosis score was determined and grouped into three risk categories: mild (score of 1), moderate (score of 2), and high risk (score of 3). For predicting the onset of pre-eclampsia, the HDP-gestosis score’s sensitivity, specificity, PPV, NPV, and diagnostic accuracy were assessed. Results: The mean age, gestational age, and BMI of the women were 25.71±5.9 years, 11.9±2.19 weeks, and 24.9±3.6 kg/m2, respectively. The gestosis score was 2 in 47.70% (n=52) of the participants, 1 in 38.53% (n=42), and ≥3 in 13.77% (n=15) of the women. Pre-eclampsia developed in 17.43% (n=19) participants. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of HDP-gestosis score for predicting pre-eclampsia were 86.66%, 96.49%, 86.91%, 97.98% and 96.12%, respectively. Conclusions: Gestosis score is a brand-new early marker for pre-eclampsia development that enables patients to receive quick care, reducing the negative effects.